Electro-Acupuncture Improve the Early Pattern Separation in Alzheimer’s Disease Mice via Basal Forebrain-Hippocampus Cholinergic Neural Circuit - Li, Long; Li, Jianhong; Dai, Yaling; Yang, Minguang; Liang, Shengxiang; Wang, Zhifu; Liu, Weilin; Chen, Lidian; Tao, Jing (Frontiers in Aging Neuroscience, 2022)
Objectives: To explore the effect of EA treatment on pattern separation and investigate the neural circuit mechanism involved in five familial mutations (5×FAD) mice. Methods: 5×FAD mice were treated with EA at Baihui (DU20) and Shenting (DU24) acupoints for 30 minutes each time, lasting for 4 weeks. Cognitive-behavioral tests were performed to evaluate the effects of EA treatment on cognitive functions. 1H-MRS, Nissl staining, immunohistochemistry, and immunofluorescence were performed to examine the cholinergic system alteration. Thioflavin S staining and 6E10 immunofluorescence were performed to detect the amyloid-β (Aβ). Furthermore, hM4Di DREADDs virus and long-term clozapine-N-oxide injection were used to inhibit the MS/VDB-DG cholinergic neural circuit. Cognitive-behavioral tests and immunofluorescence were performed to investigate the cholinergic neural circuit mechanism of EA treatment improving cognition in 5×FAD mice. Results: EA treatment significantly improved spatial recognition memory and pattern separation impairment, regulated cholinergic system via reduction neuron loss, upregulation choline/creatine, choline acetyltransferase, and vesicular acetylcholine transporter, downregulation enzyme acetylcholinesterase in 5×FAD mice. Aβ deposition was reduced after EA treatment. Subsequently, the monosynaptic hM4Di DREADDs virus tracing and inhibiting strategy shown that EA treatment activates the MS/VDB-DG cholinergic neural circuit to improve the early pattern separation. In addition, EA treatment activates this circuit to upregulating M1 receptors positive cells, and promoting hippocampal neurogenesis in DG. Conclusion: EA could improve the early pattern separation impairment by activating the MS/VDB-DG cholinergic neural circuit in 5×FAD mice, which was related to the regulation of the cholinergic system and the promotion of neurogenesis by EA treatment.